2014
DOI: 10.1002/psc.2676
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy, pharmacokinetic and biodistribution studies of the anticancer peptide CIGB‐552 in mouse models

Abstract: Accumulation of the COMMD1 protein as a druggable pharmacology event to target cancer cells has not been evaluated so far in cancer animal models. We have previously demonstrated that a second-generation peptide, with cell-penetrating capacity, termed CIGB-552, was able to induce apoptosis mediated by stabilization of COMMD1. Here, we explore the antitumor effect by subcutaneous administration of CIGB-552 in a therapeutic schedule. Outstandingly, a significant delay of tumor growth was observed at 0.2 and 0.7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…In order to produce a more stable compound, modifications in the primary structure of L2 have been made resulting in a new generation of synthetic peptide: CIGB‐552. Properties already described for L2, regarding its ability to reduce tumor volume and produce cytotoxic effect in tumor cell lines, are retained by CIGB‐552 . Moreover, we have shown that CIGB‐552 stabilized COMMD1 levels, a protein involved in copper homeostasis, sodium transport, and the NF‐κB signaling pathway .…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…In order to produce a more stable compound, modifications in the primary structure of L2 have been made resulting in a new generation of synthetic peptide: CIGB‐552. Properties already described for L2, regarding its ability to reduce tumor volume and produce cytotoxic effect in tumor cell lines, are retained by CIGB‐552 . Moreover, we have shown that CIGB‐552 stabilized COMMD1 levels, a protein involved in copper homeostasis, sodium transport, and the NF‐κB signaling pathway .…”
Section: Introductionsupporting
confidence: 56%
“…Previous results obtained for three CIGB‐552 degradation derived metabolites (referred to as 5, 1a and 3) indicated that differences in their sequence may affect their functionality . However, theoretical prediction of their cell penetrating capacity estimated by two different servers CPPpred and C2pred showed no differences on the probability of CIGB‐552 and its derived metabolites to be considered as cell‐penetrating peptides (CPPs) (Supplementary Table 1).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The tumor volume at day n (TVn) was calculated as TV (mm 3 ) = ( L − W 2)/2. The relative tumor volume at day n (RTVn) versus day 0 was expressed according to the formula: RTVn = TVn/TV 0 . Regression of tumor T/C (%) in treated versus control mice was calculated using: T/C (%) = (mean RTV of treated/control group) × 100.…”
Section: Methodsmentioning
confidence: 99%
“…Among peptides, L-2 displayed the strongest in vitro cytotoxicity in human and mouse cancer cell lines [4]. The L-2 peptide primary structure was further modified to improve its activity and specificity yielding the second generation peptide CIGB-552 [5,6].…”
Section: Introductionmentioning
confidence: 99%